2017
DOI: 10.1016/j.expneurol.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive reorganization of retinogeniculate axon terminals in dorsal lateral geniculate nucleus following experimental mild traumatic brain injury

Abstract: The pathologic process in traumatic brain injury marked by delayed axonal loss, known as diffuse axonal injury (DAI), leads to partial deafferentation of neurons downstream of injured axons. This process is linked to persistent visual dysfunction following mild traumatic brain injury (mTBI), however, examination of deafferentation in humans is impossible with current technology. To investigate potential reorganization in the visual system following mTBI, we utilized the central fluid percussion injury (cFPI) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Nuclear expression of p-c-Jun increased within 3 h post-mTBI and was consistently associated with tdTomato+ PSAI, thus reaffirming our previous findings and further supporting the use of p-c-Jun as a pan-neuronal DAI marker. Temporal assessment of tdTomato+ profiles also showed a strongly correlated, dramatic increase in anterograde axonal debris and retrograde p-c-Jun expression, thereby supporting their linkages with these anterograde changes most likely reflecting widespread axon terminal degeneration concomitant with deafferentation of target neurons (Erb and Povlishock 1991;Povlishock et al 1992;Patel et al 2016). Importantly, this neuropathology evolved without evidence of neuronal loss, consistent with the observation of tdTomato+ interneuron PSAI associated with retrograde p-c-Jun nuclear expression, indicating activation of genetic programs involving cell survival and axonal regeneration (Christman et al 1997;Raivich et al 2004;Greer et al 2011;Wang et al 2013;Patel et al 2016).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Nuclear expression of p-c-Jun increased within 3 h post-mTBI and was consistently associated with tdTomato+ PSAI, thus reaffirming our previous findings and further supporting the use of p-c-Jun as a pan-neuronal DAI marker. Temporal assessment of tdTomato+ profiles also showed a strongly correlated, dramatic increase in anterograde axonal debris and retrograde p-c-Jun expression, thereby supporting their linkages with these anterograde changes most likely reflecting widespread axon terminal degeneration concomitant with deafferentation of target neurons (Erb and Povlishock 1991;Povlishock et al 1992;Patel et al 2016). Importantly, this neuropathology evolved without evidence of neuronal loss, consistent with the observation of tdTomato+ interneuron PSAI associated with retrograde p-c-Jun nuclear expression, indicating activation of genetic programs involving cell survival and axonal regeneration (Christman et al 1997;Raivich et al 2004;Greer et al 2011;Wang et al 2013;Patel et al 2016).…”
Section: Discussionmentioning
confidence: 91%
“…Previously, we showed that DAI is a progressive axonopathy leading to overt structural disconnection followed by widespread terminal loss and Wallerian degeneration (Povlishock et al 1983;Erb and Povlishock 1991;Povlishock 1993;Christman et al 1994). Although studying diffuse changes in the fine-scale structure of neocortex is difficult (Crick 1979;Povlishock and Christman 1995), emerging evidence supports that widespread terminal loss/deafferentation of cerebral networks contributes to mTBI morbidity and sets the stage for subsequent adaptive or maladaptive plasticity (Povlishock et al 1992;Christman et al 1997;Phillips and Reeves 2001;Huang et al 2009; Marquez de la Plata et al 2011;Patel et al 2016;van der Horn et al 2016). It has been assumed that this DAI elicits cortical network disconnection primarily via the white matter (WM) tracts' vulnerability for deformation (Adams et al 1989(Adams et al , 1991.…”
Section: Introductionmentioning
confidence: 98%
“…The histologic results in the current study are similar to findings in a mouse midline fluid percussion injury model of TBI, in which damage to the optic nerve is accompanied by microglial infiltration of the optic nerve [ 48 , 49 ]. In the fluid percussion model, there is decreased innervation of the LGN at 4 days after injury, which is at least partially recovered by 10 to 20 days after injury [ 50 ]. Other groups have reported injury in the optic system after experimental blast TBI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, microglia-astrocyte coordination is likely required for axon survival and regeneration where lack of a microglial response shifts astrocytes to a pro-inflammatory state in a mouse model of demyelination [56]. Yet, studies probing the activity of glial cells during regeneration after traumatic axonal injury, in particular, are lacking [22,57]. Our data suggest that astrocytes and microglia respond differently in relation to each other within regions at each time point, such as in the LGN where astrocytes are more consistently reactive compared to microglia, with no microglial response in the dLGN vs vLGN.…”
Section: Discussionmentioning
confidence: 99%